Portfolio management using realized covariances: Evidence from Brazil - Jo\~ao F. Caldeira; Guilherme V. Moura; Marcelo S. Perlin; André A.P. Santos (EconomiA, 2017)
It is often argued that intraday returns can be used to construct covariance estimates that are more accurate than those based on daily returns. However, it is still unclear whether high frequency data provide more precise covariance estimates in markets more contaminated from microstructure noise such as higher bid-ask spreads and lower liquidity. We address this question by investigating the benefits of using high frequency data in the Brazilian equities market to construct optimal minimum variance portfolios. We implement alternative realized covariance estimators based on intraday returns sampled at alternative frequencies and obtain their dynamic versions using a multivariate GARCH framework. Our evidence based on a high-dimensional data set suggests that realized covariance estimators performed significantly better from an economic point of view in comparison to standard estimators based on low-frequency (close-to-close) data as they delivered less risky portfolios. – – Argumenta-se frequentemente que retornos intradiários podem ser usados para construir estimativas de covariâncias mais precisas em relaç\~ao àquelas obtidas com retornos diários. No entanto, ainda n\~ao está claro se os dados de alta freqüência fornecem estimativas de covariância mais precisas em mercados mais contaminados pelo ruído da microestrutura, como maiores spreads entre ofertas de compra e venda e baixa liquidez. Abordamos essa quest\~ao investigando os benefícios do uso de dados de alta freqüência no mercado de aç\~oes brasileiro através da construç\~ao de portfólios ótimos de variância mínima. Implementamos diversos estimadores de covariâncias realizadas com base em retornos intradiários amostrados em diferentes frequências e obtemos suas vers\~oes dinâmicas usando uma estrutura GARCH multivariada. Nossa evidência baseada em um conjunto de dados de alta dimens\~ao sugere que os estimadores de covariâncias realizadas obtiveram um desempenho significativamente melhor do ponto de vista econômico em comparaç\~ao com os estimadores baseados em dados de baixa freqüência (baseados em dados de fechamento) uma vez que geraram portfólios menos arriscados."
Keywords: 330; BEKK specification; Bootstrap test; Liquidity; Tick by tick data; Turnover; Especificaç\~ao BEKK; Bootstrap; Liquidez; Dados negócio a negócio; Turnover